Hizikia fusiforme functional oil (HFFO) prevents neuroinflammation and memory deficits evoked by lipopolysaccharide/aluminum trichloride in zebrafish - Nie, Ying-Ying; Zhou, Long-Jian; Li, Yan-Mei; Yang, Wen-Cong; Liu, Ya-Yue; Yang, Zhi-You; Ma, Xiao-Xiang; Zhang, Yong-Ping; Hong, Peng-Zhi; Zhang, Yi (Frontiers in Aging Neuroscience, 2022)
Background: Oxidative stress, cholinergic deficiency and neuroinflammation are hallmarks in most neurodegenerative disorders (NDs). Lipids play an important role in brain development and proper functioning. Marine derived lipids have shown good memory improving potentials especially those from fish and microalgae. The cultivated macroalga Hizikia fusiforme is a healthy food and shows benefits to memory, but study is rare on the brain healthy value of its oil. Previously, we had reported that the Hizikia fusiforme functional oil (HFFO) containing arachidonic acid, 11,14,17-eicosatrienoic acid, phytol, and other molecules displayed in vitro acetylcholinesterase inhibitory and nitroxide scavenging activity; however, the in vivo effect remains unclear. In this study, we further investigated its potential effects against lipopolysaccharides (LPS) or aluminum trichloride (AlCl3) induced memory deficiency in zebrafish and its drug related properties in silica. Methods: We established memory deficits models in zebrafish by intraperitoneal (i.p.) injection of lipopolysaccharides (LPS) (75 ng) or aluminum trichloride (AlCl3) (21 μg), and assessed their behaviors in the T-maze test. The interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), acetylcholine (ACh) and malondialdehyde (MDA) levels were assayed as markers of inflammation, cholinergic activity, and oxidative stress 24 h after the LPS / AlCl3 injection. Besides, the interaction of two main components 11,14,17-eicosatrienoic acid and phytol with the important anti-inflammatory targets nuclear factor kappa B (NF-κB) and cyclooxygenase 2 (COX-2) were investigated by molecular docking. Specifically, the absorption, distribution, metabolism, excretion, and toxicity (ADMET) and drug-likeness properties of HFFO were studied by ADMETlab. Results: The results showed that HFFO reduced cognitive deficits in zebrafish T-maze induced by LPS / AlCl3. While the LPS / AlCl3 treatment increased MDA content, lowered ACh levels in zebrafish brain, and elevated levels of central and peripheral proinflammatory cytokines, these effects were reversed by 100 mg/kg HFFO except for MDA. Moreover, 11,14,17-eicosatrienoic acid and phytol showed good affinity with NF-κB and COX-2 and HFFO exhibited acceptable drug-likeness and ADMET profiles in general. Conclusion: Collectively, the present findings suggest HFFO as a potent neuroprotectant potentially valuable for the prevention of memory impairment caused by cholinergic deficiency and neuroinflammation.